2022
DOI: 10.1002/smtd.202200321
|View full text |Cite
|
Sign up to set email alerts
|

Single Image Capture of Bioactive Ion Crosstalk within Inter‐Organelle Membrane Contacts at Nanometer Resolution

Abstract: mitochondria and lysosomes, thus regulating numerous cellular processes, most notably those involved in the maintenance of cellular homeostasis. [3][4][5][6][7][8][9][10][11] Moreover, the mounting evidence implicates the breakdown in mitochondria-lysosome interorganelle cross-talk as relevant in number of human pathologies, most notably neurodegenerative disease, such as Parkinson's disease. [3] Therefore, understanding MLC processes and the key molecules involved in mediating inter-organelle communication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…After shaking for 2 h, the absorption wavelength of each well was measured at 450 nm by an enzyme labeling apparatus (BioTek Synergy HTX; Agilent Technologies, Inc., Beijing, China). Cell viability (%) was calculated by the mean absorbance value of the treatment group divided by the mean absorbance value of the control group [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…After shaking for 2 h, the absorption wavelength of each well was measured at 450 nm by an enzyme labeling apparatus (BioTek Synergy HTX; Agilent Technologies, Inc., Beijing, China). Cell viability (%) was calculated by the mean absorbance value of the treatment group divided by the mean absorbance value of the control group [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The 96-well plate medium was discarded, and the cells were washed twice with PBS. Media containing different concentrations of Fe-MOF (0.5–50 μg/mL) were then added to each well and incubated for 24 h. Cell viability was determined using the MTT assay according to standard protocols ( Javad Farhangi et al, 2021 ; Liu et al, 2021 ; Fang et al, 2022 ; Ji et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Fang et al reported another hemicyanine-based fluorogenic probe, CHS , with good solubility due to the sulfonic acids, which responded to mitochondrial ( λ em = 493 nm) and lysosomal ( λ em = 674 nm) RSS by emitting different fluorescence wavelengths. 176 This probe enabled the visualization of mutual RSS alterations, establishing the role of RSS in intercellular organelle interaction (Table 2).…”
Section: Small-molecule Fluorogenic Probes For Mitochondrial Srimentioning
confidence: 99%